Physical activity and influencing factors in people post stroke or transient ischemic attack across diverse regions in Sweden - Bezuidenhout, Lucian; Humphries, Sophia; Moulaee Conradsson, David (Frontiers in Neurology, 2024)
Background and purpose Physical activity (PA) and sedentary behavior are key targets for secondary stroke prevention, yet their characteristics and contributing factors are not well understood. This study aims to explore PA and sedentary behavior in individuals' post-stroke or transient ischemic attack (TIA) and identify factors linked to low PA (≤5,000 steps/day) and prolonged sedentary time (≥8 h/day). Methods A cross-sectional study comparing sensor-derived (activPAL) PA and sedentary time among community-dwelling individuals post stroke or TIA residing in diverse geographical regions of Sweden. Multiple logistic regression models were performed to determine potential factors associated with low PA and prolonged sedentary time. Results The study included 101 participants post-stroke (n = 68) and TIA (n = 33), with a mean age of 70.5 years (65% female), mostly with no or mild disability (91%), living in metropolitan (69%) and rural (31%) areas of Sweden. Most participants (72%) had ≥ 8 h of sedentary time per day and 38% performed ≤5,000 steps per day. Using a walking aid (OR = 11.43, p = 0.002) was independently associated with low PA, whereas contextual factors; living alone (OR = 3.49, p = 0.029) and living in metropolitan areas (OR = 2.79, p = 0.036), were associated with prolonged sedentary time. Discussion and conclusions In this study encompassing people post stroke or TIA from diverse geographical regions across Sweden, PA was associated with mobility status whereas sedentary behavior was associated with contextual factors. The results also showed a large variation in PA highlighting the need for tailored strategies to promote PA post stroke or TIA.